Approach to medical missions: Dr. Neil Macvicar and the Victoria Hospital, Lovedale, South Africa, circa 1900-1950 - Lunde, Martin Jacob (The University of Edinburgh, 2009)
This thesis examines the thought, work, and impact of the Scottish medical missionary, Dr Neil Macvicar, as well other personnel connected to the Victoria Hospital at the Lovedale mission in the Eastern Cape. Of special concern for study in medical history, missiology, and relief development studies, this work centres on Macvicar’s modern Western conceptions of Christianity, biomedicine, civilisation, African cosmological understandings, and traditional methods of healing, within the last years of the Cape Colony and the early history of the Union of South Africa. Macvicar was heavily influenced by the scientific advances and thought of his day, which in turn shaped his perceptions and attitudes not only to African worldviews but to his form and expression of Western Christianity and mission work. His efforts to eradicate and replace ‘superstitious’ thought and ‘inadequate’ methods of treatment focussed especially on the training of an African elite, including the first certified black nurses and largely unsuccessful attempts to initiate a scheme for black doctors. In addition, he promoted public health education endeavours; was heavily involved with patient care and treatment; enabled the inception of the South African Health Society; contributed countless articles, pamphlets, reviews, and books – both scholarly and popular; and was a central figure in the formation of the South African Native College (later to become Fort Hare University). As well as Macvicar, this thesis draws upon and exposes the impact of more marginalised medical personnel, such as Jane Waterston, one of the first female physicians in the modern British scheme, and Govan Koboka, a South African medical dispenser. Their work at Lovedale, among others like them in the late 19th century, was the primary approach to Western biomedical treatment offered by the mission, though largely unacknowledged in wider historical studies. This work also reveals how the hospital operated not simply as a place for healing, or indeed of dying, but as a ‘sacred’ or religious space in addition to its role as an educational centre for patients, and place for the training of other missionaries. Finally, elements of hospital-based biomedical practices, such as surgery, are examined and the Influenza Pandemic of 1918-1919 is looked at as a case study of mission community response to catastrophic disease.
Keywords: medical missionaries; MacVicar, Neil; missiology; biomedicine; South Africa; Scottish missionaries; public health education